THE ANALYSIS OF LECTURERS’ PERFORMANCE IN PAMULANG UNIVERSITY - Mukrodi Mukrodi (Sekolah Menengah Kejuruan (SMK) Pustek, 2018)
The purpose of this study is to analyze lecturer’s performance at Pamulang University. The research design used in the preparation of this study is quantitative causal associative with descriptive explanation. The analysis method used is structural equation modeling with sampling technique used is random sampling. Partially recruitment has a positive and significant effect on lecturer performance with regression coefficient of 0,27. Selection has a positive and significant effect on lecturer performance with regression coefficient of 0,50. Simultaneously recruitment and selection have a positive and significant effect on lecturer performance of 0,55